Deviations from 1:1 and numbers of progeny necessary for establishing linkage - David D. Perkins (Fungal Genetics Reports, 1994)
We have found the following table useful when assigning new genes to linkage groups, either with Parental:Recombinant random isolates or with Parental ditype:Nonparental ditype tetrads. The ratios for total numbers through 50 are from Perkins, D.D. 1953 Genetics 38:187-197, and were extracted from tables in Warwick, B.L. Texas Agric. Exper. Sta. Bull. 463:1-28. The ratios for total numbers from 51-100 were obtained using binomial probability paper (Mosteller, F., and J.W. Tukey. J. Amer. Stat. Assoc. 44:174-212).